Análise do uso de glossários terminológicos no processo de ensino e aprendizagem de estudantes surdos no Curso de Letras - Língua Portuguesa e Libras da UFRN - Farias, Mariana Damião (2022)
In this study, we sought to analyze the pedagogical implications of the use of terminological glossaries, products that cover a set of terms or vocabulary of a particular specialty, in the teaching and learning process of deaf students of the Licentiate Degree in Languages – Portuguese and Brazilian Sign Language (Libras) of UFRN, as well as identifying the processes of production of glossaries and their use, characterizing the terminological glossaries in Libras concerning the course and analyzing the use of terminological glossaries in Libras and their relationship with the teaching and learning process of deaf students. The research involved a deaf professor and three deaf students from a class of a curricular component of that graduation. In view of the New Coronavirus pandemic, data collection was carried out through video recording of the synchronous classes of the aforementioned class, online questionnaires and autoscopy sessions with the class teacher, carried out on a digital platform. Thus, it was decided to carry out a research with a qualitative approach, interpretive paradigm, descriptive nature and with elements of a case study. The research design is structured based on the Autoscopy procedures, with the teacher performing the self-analysis of video recordings of her own classes, and the data content analysis is subsidized in the Dialogic Discourse Analysis, theoretical current of the Bakhtin Circle. The results were presented through two categories of analysis: 1) autoscopy and the use of terminological glossaries in the teaching of deaf students, which sought to highlight the reflection of the teacher's practice throughout the classes and sought to identify how the glossary relates to the teaching process by the teacher, and 2) use of terminological glossaries in the learning of deaf students, to point out the learning process of deaf students through the relationship with glossaries. The results found allow us to highlight important aspects in the favorable pedagogical implications of the use of terminological glossaries in the teaching and learning process of deaf students in the Licentiate Degree Course in Languages – Portuguese and Libras at UFRN, such as the potential versatility of this material in teaching pedagogical strategies and the educational value of this bilingual consultation product to help deaf students learn Portuguese as a second language, as they see the terminology glossary as a clearer, more direct and practical source of help for their use in studies. The study pointed to the need to carry out more scientific researches with regard to autoscopy in the training of deaf teachers, the production of more glossaries and the use of glossaries as bilingual teaching materials in educational contexts other than the one researched. However, it is important to consider that the changes are gradual, as they imply ruptures of concepts and practices rooted over time and that do not take place immediately.